Contribution of eccentric strength to cutting performance in female soccer players - Jones, P. A.; Dos`Santos, T.; McMahon, J. J.; Graham-Smith, P. (The Journal of Strength and Conditioning Research, 2022)
The aim of this study was to examine the contribution of eccentric strength to performance of a 70-90° cutting task (CUT) (time to complete: 5 m approach, 70-90° cut, 3 m exit). Nineteen female soccer players (mean ± SD age, height, and mass; 21.7 ± 4.3 years, 1.67 ± 0.07 m, and 60.5 ± 6.1 kg) from the top 2 tiers of English women's soccer participated in the study. Each player performed 6 trials of the CUT task whereby three-dimensional motion data from 10 Qualisys proreflex cameras (240 Hz) and ground reaction forces from 2 Advanced Mechanical Technology, Inc. force platforms (1,200 Hz) were collected. Relative eccentric knee extensor (ECC-KE) and flexor peak moments (ECC-KF) were collected from both limbs at 60°·s-1 using a Kin-Com isokinetic dynamometer. Hierarchical multiple regression revealed that minimum center of mass (CM) and approach velocities (CM velocity at touchdown of penultimate foot contact) could explain 82% (79% adjusted) of the variation in CUT completion time (F(1,16) = 36.086, p < 0.0001). ECC-KE was significantly (p < 0.05) moderately associated (R = 0.610) with velocities at key instances during the CUT. High (upper 50th percentile) ECC-KE individuals (n = 9) had significantly (p = 0.01; d = 1.34) greater velocities at key instances during the CUT. The findings suggest that individuals with higher ECC-KE produce faster CUT performance, by approaching with greater velocity and maintaining a higher velocity during penultimate and final contact, as they are better able to tolerate the larger loads associated with a faster approach.